KOORDINASI PEMERINTAH DAERAH TERHADAP URUSAN LINGKUNGAN HIDUP : STUDI KASUS LIMBAH PETERNAKAN BABI DI KECAMATAN SIAK HULU – KABUPATEN KAMPAR - Robyal Maldini; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Pig farms in Pandau Jaya Village, Siak Hulu District, Kampar Regency, Riau Province with dozens of livestock are troubling residents. Its existence results in air pollution and scattered waste. However, this seems permissible. Because, until now there is no prohibition or relocating the farm. This study seeks to determine the coordination between the Environmental Service of Kampar Regency and Siak Hulu District and Pandau Jaya Village. This study uses a qualitative approach with a descriptive method. In collecting data, the author uses interview and documentation techniques. After the required data is obtained, the data is grouped and described according to its type and analyzed using qualitative analysis. The results of the study explain that the Regional Government Coordination between the District Environmental Service and Pandau Jaya Village on Pig Farm Waste in Pandau Jaya Village, Siak Hulu District according to 3 Coordination indicators (1) Agency Effort, (2) Unity of Action, and (3) Common Purposes. The results of the study indicate that in coordinating so far, they have worked by making efforts in dealing with waste from the pig farm by holding meetings. However, there are still shortcomings, namely in involving inter-agency efforts and taking an action is still constrained due to unclear laws. Then in achieving common goals between agencies, efforts have been made to achieve effective results even though they have not been fully resolved. Keywords: Coordination, Pig Farming Waste